COMPARISON OF LUNAR WITH TERRESTRIAL AND METEORITIC ROCKS - Turner, Francis J. (1969)
This note examines critically recent attempts to identify or closely correlate lunar surface samples—on the basis of alpha-scattering analysis—with terrestrial igneous rocks (basalts) or with eucrite meteorites. Basalts show considerable variety; but all have chemical characteristics inherited from terrestrial mantle rock melted under a limited range of terrestrial pressure-temperature conditions. What is characteristic is not so much the content of any particular element or oxide—e.g., SiO(2) 47-52 per cent—but rather a complete chemical pattern in which such ratios as Fe/Mg and Ca/(Na + K) show consistent relationships to Si content. These are the chemical criteria that might be useful in comparing terrestrial basalt with extraterrestrial rocks. Basalts also have distinctive mineralogical and textural characteristics; and if a lunar or meteoritic rock is to be identified as basalt it must possess these, too. Turkevich's analysis of alpha-scattering data for lunar samples (Surveyor V) show significant departure from basaltic composition: Very high (Ca + K)/Na associated with distinctly high Fe/Mg. In basalts relatively high (Ca + K)/Na—in no case approaching the reported lunar values—tends to be associated with Fe/Mg values lower than average. The same “lunar” pattern of high (Ca + K)/Na and Fe/Mg appears in recorded analyses of eucrite meteorites. In the lunar samples, Ti is notably higher than in basalts, and even more so than in eucrites. If eucrites are of lunar origin their Ti values are, so far, a real anomaly.